(untitled) (Bangladesh Medical Journal, 2017)
Here we describe a case of a 20-year-old, otherwise healthy man, who consulted a physician due to acute low back pain presenting for a couple of days. Pain appeared suddenly, without any preceding trauma. Physical examination was unremarkable. Initial laboratory tests showed elevated inflammatory marker and thrombocytopenia. Patient was treated conservatively but due to increasing pain MRI of spine with contrast was advised which showed feature suggestive of infiltrative disease. Eventually patient was diagnosed as a case of acute lymphoblastic leukaemia on further peripheral blood film and bone marrow study. Bangladesh Med J. 2017 Jan; 46 (1): 41-43